PsycEXTRA Dataset 2005
DOI: 10.1037/e479862006-001
|View full text |Cite
|
Sign up to set email alerts
|

Sex Between Young Teens and Older Individuals: A Demographic Portrait

Abstract: Over the past decade, considerable legal and policy discussion has emerged about sexual activity between young teens and older individuals. This discussion has been prompted by the growing awareness of the personal and societal costs of this activity. Sex between young teens and older individuals is linked with risky sexual behaviors that could lead to unintended pregnancy and childbearing, as well as to sexually transmitted infections. Among sexually experienced teens, having sex with someone who is older has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 8 publications
2
32
0
2
Order By: Relevance
“…Thus, young female teenagers who have sex with an older partner have an elevated risk of childbearing outside marriage partly because of their number of sexual partners in adolescence. This finding supports other research linking sex with older partners with an increased number of sexual relationships, 12,18 and supports an association between a greater number of sexual partners and adverse outcomes such as reduced contraceptive use and increased teenage pregnancy risk. 14 In addition, for females, having ever had a nonromantic partner is associated with increased odds of acquiring an STD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, young female teenagers who have sex with an older partner have an elevated risk of childbearing outside marriage partly because of their number of sexual partners in adolescence. This finding supports other research linking sex with older partners with an increased number of sexual relationships, 12,18 and supports an association between a greater number of sexual partners and adverse outcomes such as reduced contraceptive use and increased teenage pregnancy risk. 14 In addition, for females, having ever had a nonromantic partner is associated with increased odds of acquiring an STD.…”
Section: Discussionsupporting
confidence: 89%
“…Yet, more than one-quarter of teenagers whose first sexual relationship occurred before age 16 with a partner three or more years their senior were male. 12 Findings for males have been mixed: One study showed poorer contraceptive use among males who had had older partners, 4 and another showed no association. 7 Therefore, it is important to investigate the influence of age and partners' age difference on both males' and females' sexual health risks using longitudinal data.…”
mentioning
confidence: 99%
“…Sexual activity for any teenage girl is risky due to multiple factors such as elevated risk of sexually transmitted infections (STI) and unwanted pregnancy. Girls who experience sex at the age of 15 years or younger are a particularly high risk subset for other physical and psychosocial health problems 4. These younger girls have been found to be more likely than boys to have sex with an older individual and more likely to be a victim of instances of involuntary or unwanted sex 4,5.…”
Section: Introductionmentioning
confidence: 99%
“…Girls whose sexual debut occurred with an older partner were twice as likely to report it was not voluntary than girls whose first sexual partner whose age was similar . In addition, more than 50% of girls 14 or younger who had sex reported their partners to be at least 3 years older at the time of intercourse …”
mentioning
confidence: 99%
“…20 In addition, more than 50% of girls 14 or younger who had sex reported their partners to be at least 3 years older at the time of intercourse. 21 Adolescents who became sexually active earlier than their peers are more likely to report using drugs or alcohol at last intercourse and are also more likely to develop a substance use disorder. 5,22,23 Among sexually active high school students, over 21% reported using drugs or alcohol during their most recent sexual encounter.…”
mentioning
confidence: 99%